(untitled) (Libellarium: journal for research in the field of information and related sciences, 2021)
The aim of this paper was to explore the issue of library borrowing of books written by Croatian authors. The focus was on the most borrowed books. In the first part of the paper there is a literature review related to the topic, such as readers’ preferences and the importance of culturally diverse materials. Following the presentation of theoretical background, the second part of the paper presents the research findings. The research goals were as follows: 1) to explore how often the users of Croatian public libraries have borrowed books written by authors from Croatia in comparison to books by non-Croatian authors; 2) to explore the characteristics of the most borrowed books by Croatian authors (when they were published; the gender of the authors; if they are fiction, non-fiction or picture books; what their genres are). The public libraries in Zagreb, Split, Rijeka and Pula were included in the research. The findings indicate that there are about 10% of books by Croatian authors among the 2,000 most borrowed books in the listed libraries. The majority of the books are fiction books published for the first time after the year 2000.